2016
DOI: 10.5114/aoms.2016.61918
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic macular edema, retinopathy and age-related macular degeneration as inflammatory conditions

Abstract: Diabetic macular edema (DME) and diabetic retinopathy (DR) are complications affecting about 25% of all patients with long-standing type 1 and type 2 diabetes mellitus and are a major cause of significant decrease in vision and quality of life. Age-related macular degeneration (AMD) is not uncommon, and diabetes mellitus affects the incidence and progression of AMD through altering hemodynamics, increasing oxidative stress, accumulating advanced glycation end products, etc. Recent studies suggest that DME, DR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 167 publications
(154 reference statements)
1
38
0
Order By: Relevance
“…Mechanisms underlying the protective action of mFAG are difficult to postulate and their elucidation needs additional work. One possibility is that fatty acid mixture supplementation reinstates the deficiency of anti-inflammatory bioactive lipids that play a predominant role in AMD [ 50 ]. In this respect, polyunsaturated fatty acid (PUFA) administration has been shown to counteract several neovascular pathologies of the eye through different actions.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms underlying the protective action of mFAG are difficult to postulate and their elucidation needs additional work. One possibility is that fatty acid mixture supplementation reinstates the deficiency of anti-inflammatory bioactive lipids that play a predominant role in AMD [ 50 ]. In this respect, polyunsaturated fatty acid (PUFA) administration has been shown to counteract several neovascular pathologies of the eye through different actions.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of intraocular angiogenesis is further orchestrated by the increase of proangiogenic factors, mainly VEGF in the retinal neurons and RPE cells [ 95 ]. Untreated condition in the patients can lead to massive degradation in the basal endothelium membrane, neovascularization, and functional disruption of the neurosensors in the retina [ 107 ].…”
Section: Mscs Modulates Angiogenic Activity In Retinal Diseasesmentioning
confidence: 99%
“…It is noteworthy that metabolic dysregulation in diabetic patients involves an uncontrollable increase in blood glucose (hyperglycemia) and cholesterol (hyperlipidemia) levels which stimulate VEGF secretion and ultimately contribute to the pathological alteration in the retinal vasculature integrity [ 107 ]. Ezquer et al, 2016 previously reported no apparent changes in pro-angiogenic expression observed upon administration of MSC in diabetic-induced mice model [ 51 ].…”
Section: Mscs Modulates Angiogenic Activity In Retinal Diseasesmentioning
confidence: 99%
“…Diabetic retinopathy (DR) and wet age-related macular degeneration (AMD) are two retinal diseases that are caused by vascular leakage and angiogenesis. 3 Breakdown of inner BRB is a common pathologic feature in patients with diabetes and experimental animal models. DR is a common microvascular complication of diabetes mellitus and is one of the fastest growing causes of blindness and visual impairment in the working age populations, whereas AMD mainly affects aged populations.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Blocking the vascular endothelial growth factor (VEGF) signaling pathway is the current standard pharmacological therapy for both DR and wet AMD. 3 However, anti-VEGF treatments require frequent and long-term pharmacologic administration to maintain vision gains, and although many patients respond well to anti-VEGF therapy, some have only a moderate or poor response and patients may lose their initial vision gains over time. [8][9][10] Therefore, the development of new drugs for DR and AMD is vital.…”
Section: Introductionmentioning
confidence: 99%